1985
DOI: 10.1159/000110217
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Assessment of the Prevalence Ratio of Epilepsy Adequately Adjusted by Influencing Factors

Abstract: The prevalence of epilepsy was estimated by defining an initial prevalence ratio based on a population study and modifying this figure on the basis of various factors which influenced it. The definition required 3 seizures diagnosed by a doctor and the influencing factors included false-negative responses (where the diagnosis was confirmed), false reporting (where the diagnosis had not been established) and falsely low seizure counts (where therapy had reduced the number of seizure below the mandatory 3). As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…The estimated median prevalence of epilepsy in Arab countries is 2.3/1,000 (varying from 0.9–6.5/1,000), which is just within the range found in Europe, North America, Australia, and Asia (3–8/1,000) (Beran et al., 1985; Hauser et al., 1991; Sridharan & Murthy, 1999; Forsgren et al., 2005; Mac et al., 2007), but less than in sub‐Saharan Africa (15/1,000) (Preux & Druet‐Cabanac, 2005) and Latin America (18/1,000) (Burneo et al., 2005). However, the Libyan and Sudanese studies reported a lower prevalence than expected, which is again likely to be methodologic.…”
Section: Discussionmentioning
confidence: 61%
“…The estimated median prevalence of epilepsy in Arab countries is 2.3/1,000 (varying from 0.9–6.5/1,000), which is just within the range found in Europe, North America, Australia, and Asia (3–8/1,000) (Beran et al., 1985; Hauser et al., 1991; Sridharan & Murthy, 1999; Forsgren et al., 2005; Mac et al., 2007), but less than in sub‐Saharan Africa (15/1,000) (Preux & Druet‐Cabanac, 2005) and Latin America (18/1,000) (Burneo et al., 2005). However, the Libyan and Sudanese studies reported a lower prevalence than expected, which is again likely to be methodologic.…”
Section: Discussionmentioning
confidence: 61%
“…A prevalence of 6.8 per 1000 is reported from the United States (Hauser et al. , 1991) and 7.5 per 1000 from Australia (Beran et al. , 1985).…”
Section: Discussionmentioning
confidence: 99%
“…A few researchers have defined the term "epilepsy" to include patients with a single seizure, [27][28][29] and a few have required three unprovoked seizures. 30,31 Most recent clinical and epidemiologic studies have required two unprovoked seizures as a minimal criterion for the diagnosis. 16,31 The international classification of epileptic syndromes proposed by the International League against Epilepsy categorizes patients with only a single convulsive episode separately from those with more than one seizure.…”
Section: Discussionmentioning
confidence: 99%